The Analysis of Improving Student Learning Outcomes Using The Value Clarification Technique Learning Model - Dina Destari; Hartin Kurniawati; Agnes Tesalonika Yolanda; Hendy Tannady; Magdalena Magdalena (Journal on Education, 2023)
In this investigation, scholars employed the approach of class action research (CAR). The aim of this investigation is to boost students' academic performance by utilizing the value clarification technique (VCT) as a learning model. The instruments employed in this research included observation checklists, field notes, and evaluations (pre-test and post-test). The results of this study demonstrate that incorporating the value clarification technique (VCT) as a learning model can enhance students' academic achievements, as evidenced in both the initial and subsequent stages. In the initial phase, the mean score of the pretest was more than 40, which subsequently increased to more than 60 in the posttest score. While in the subsequent phase, the mean score of the pretest was more than 50, which escalated to more than 80 in the posttest score. In the initial phase, some students scored below the KKM, but in the subsequent phase, the lowest score was 80, and no student scored below the KKM.